1984
DOI: 10.1007/bf00236219
|View full text |Cite
|
Sign up to set email alerts
|

Ascending projections from the nucleus of the brachium of the inferior colliculus in the cat

Abstract: Ascending projections from the nucleus of the brachium of the inferior colliculus (NBIC) in the cat were studied by the autoradiographic tracing method. Many fibers from the NBIC ascend ipsilaterally in the lateral tegmentum along the medial border of the brachium of the inferior colliculus. At midbrain levels, fibers from the NBIC end in the superior colliculus, the pretectum, the central gray and the peripeduncular tegmental region bilaterally with ipsilateral predominance. NBIC fibers to the superior collic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 23 publications
2
42
2
Order By: Relevance
“…In contrast, Edwards et al (1979) reported that, in the cat, the BIN projects only to the contralateral SC. This finding is inconsistent with the results of the present study as well as those of other previous tracing studies carried out on a range of species, including cats (van Buskirk, 1983;Kudo et al, 1984;Wallace and Fredens, 1989), and may reflect a difference in the criteria used for defining the borders of the BIN. These anatomical studies are supported by evidence for a functional connection between the IC and the SC.…”
Section: Auditory Inputs To the Superior Colliculuscontrasting
confidence: 82%
See 1 more Smart Citation
“…In contrast, Edwards et al (1979) reported that, in the cat, the BIN projects only to the contralateral SC. This finding is inconsistent with the results of the present study as well as those of other previous tracing studies carried out on a range of species, including cats (van Buskirk, 1983;Kudo et al, 1984;Wallace and Fredens, 1989), and may reflect a difference in the criteria used for defining the borders of the BIN. These anatomical studies are supported by evidence for a functional connection between the IC and the SC.…”
Section: Auditory Inputs To the Superior Colliculuscontrasting
confidence: 82%
“…Some of these studies did not identify which regions of the IC provide the SC afferents (Moore and Goldberg, 1966;Tarlov and Moore, 1966;Powell and Hatton, 1969;Cadusseau and Roger, 1985), whereas others reported SC inputs originating in the BIN (Edwards et al, 1979;van Buskirk, 1983;Kudo et al, 1984;Wallace and Fredens, 1989), ICX (Edwards et al, 1979;Kudo and Niimi, 1980;van Buskirk, 1983;Hashikawa and Kawamura, 1983;Druga and Syka, 1984;Covey et al, 1987;Zhang et al, 1987), ICP (Edwards et al, 1979;Hashikawa and Kawamura, 1983), and ICC (Druga and Syka, 1984;Covey et al, 1987;Zhang et al, 1987). The majority of these studies described inputs either predominantly or exclusively from regions of the ipsilateral IC.…”
Section: Auditory Inputs To the Superior Colliculusmentioning
confidence: 91%
“…In the nucleus of the BIC, the percentage of projection neurons with GABA-positive immunoreactivity was small. The weak projection to the dorsal MGB and the absence of a projection to the ventral MGB (Kudo et al, 1984) make the nucleus of the brachium an unlikely source of our observed inhibitory synaptic events. The reticular formation (including the cuneiform nucleus) also had projection neurons to the MGB; however, the vast majority of the projection neurons did not contain GABA.…”
Section: Sources Of the Gabaergic Inhibition In The Mgbmentioning
confidence: 85%
“…Indeed, the PO receives auditory inputs from the external, pericentral, and brachial nuclei of the inferior colliculus (Kudo and Niimi, 1980;Kudo et al, 1984;Linke et al, 2000) as well as the dorsal nucleus of the lateral lemniscus (Kudo et al, 1983). In addition, PO receives visual and somatosensory inputs from the superior colliculus and spinal cord (for review, see Jones, 1985).…”
Section: Introductionmentioning
confidence: 99%